2004
DOI: 10.1111/j.1945-5100.2004.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Early fracturing and impact residue emplacement: Can modelling help to predict their location in major craters?

Abstract: Abstract-Understanding the nature and composition of larger extraterrestrial bodies that may collide with the Earth is important. One source of information lies in the record of ancient impact craters, some of which have yielded chemical information as to the impacting body. Many deeply eroded craters have no remaining melt sheet or ejecta yet may contain impactor residue within basement fractures. The emplacement mechanism for fractionated siderophile residues is likely to be gaseous, although, melt droplets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…The MEMIN experiments yielded results that are very similar to observations in nature, e.g., at Meteor Crater and the Wabar craters (Kearsley et al. ; Mittlefehldt et al. ; Hamann et al.…”
Section: Projectile–target Interactionsupporting
confidence: 74%
“…The MEMIN experiments yielded results that are very similar to observations in nature, e.g., at Meteor Crater and the Wabar craters (Kearsley et al. ; Mittlefehldt et al. ; Hamann et al.…”
Section: Projectile–target Interactionsupporting
confidence: 74%
“…1976; Hörz et al. 1989), Monturaqui crater (e.g., Bunch and Cassidy 1972; Kearsley et al. 2004), and Kamil crater (D’Orazio et al.…”
Section: Discussionmentioning
confidence: 99%
“…In impact melts of Meteor Crater (Arizona, USA), Hörz et al. (2002) and Kearsley et al. (2004) described a decrease in Fe/Ni in meteoritic droplets compared with the composition of the Canyon Diablo meteorite, and a complementary increase in this ratio in the surrounding target melt.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Son and Koeberl (2007) reported detail analyses of 67 impact melt samples collected from the ejecta blanket around the crater rim, but no enrichment of any meteoritic component was seen. Kearsley et al (2004), however, reported the presence of small (<10 µm) iron-nickel particles with a wide range of Fe/Ni ratios (0.02-14.4) within vesicles of Lonar impact melts, but it is not clear whether these fragments represent an indigenous component (may be reduced during impact) or an extraterrestrial contamination (Osae et al 2005). Further work by Son and Koeberl (2007), however, does not confirm any presence of iron-nickel particles within Lonar impact melts.…”
Section: Introductionmentioning
confidence: 92%